Understanding lived experience through thematic analysis in international social work - Nkire, Chiamaka (My University, 2026)
In this paper presentation, I explore my experiential learning through qualitative analysis in an international social work study examining student exchange experiences between Canada and Germany (Ouedraogo & Wedler, 2019). My contribution centred on engaging with Braun and Clarke’s (2006) six-steps thematic analysis process, which involves familiarizing oneself with the data, generating codes, searching for themes, reviewing themes, defining and naming themes, and producing the report. Working closely with interview transcripts allowed me to see how lived experience becomes a source of knowledge in qualitative inquiry, where meaning is shaped through context, interpretation, and reflexive engagement (Barrell, 2020). This analytical experience deepened my awareness of ethical responsibility in representing participants’ narratives and highlighted how my cultural and educational background influences interpretation. It also strengthened my understanding of international social work as a field shaped by globalization, cross-cultural exchange, and experiential forms of learning. This presentation synthesizes how participating in thematic analysis supported my academic development and expanded my understanding of knowledge construction in international social work practice and education.
Presented on April 23, 2026, at Student Research Day, held at MacEwan University in Edmonton, AB.
Keywords: international social work; lived experience; qualitative; reflexivity; thematic analysis; Student Research Day